Substrate-immobilized electrospun TiO2 nanofibers for photocatalytic degradation of pharmaceuticals: The effects of pH and dissolved organic matter characteristics - Maeng, Sung Kyu; Cho, Kangwoo; Jeong, Boyoung; Lee, Jaesang; Lee, Yunho; Lee, Changha; Choi, Kyoung Jin; Hong, Seok Won (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
A substrate-immobilized (SI) TiO2 nanofiber (NF) photocatalyst for multiple uses was prepared through electrospinning and hot pressing. The rate of furfuryl alcohol degradation under UV irradiation was found to be the highest when the anatase to rutile ratio was 70:30; the rate did not linearly increase as a function of the NF film thickness, mainly due to diffusion limitation. Even after eight repeated cycles, it showed only a marginal reduction in the photocatalytic activity for the degradation of cimetidine. The effects of pH and different organic matter characteristics on the photodegradation of cimetidine (CMT), propranolol (PRP), and carbamazepine (CBZ) were investigated. The pH-dependence of the photocatalytic degradation rates of PRP was explained by electrostatic interactions between the selected compounds and the surface of TiO2 NFs. The degradation rates of CMT showed the following order: deionized water > L-tyrosine > secondary wastewater effluent (effluent organic matter) > Suwannee River natural organic matter, demonstrating that the characteristics of the dissolved organic matter (DOM) can affect the photodegradation of CMT. Photodegradation of CBZ was affected by the presence of DOM, and no significant change was observed between different DOM characteristics. These findings suggest that the removal of CMT, PRP, and CBZ during photocatalytic oxidation using SI TiO2 NFs is affected by the presence of DOM and/or pH, which should be importantly considered for practical applications. (c) 2015 Elsevier Ltd. All rights reserved.